Law Enforcement In Regional Head Elections Regarding Campaigns Conducted Through Social Media In Barru Regency - Asrul Asrul; La Ode Husen; Azkari Razak (Fakultas Hukum Dehasen, 2024)
The research aims to: 1) find out and analyze measures to prevent violations of campaigns via social media, and 2) To find out and analyze the factors influencing law enforcement against campaigns via social media. This type of research is empirical and sociological juridical law, data obtained by the author from document studies and interviews with interested parties, in this case, the Barru Regency BAWASLU, namely the Bawaslu chairman, members and staff of the Regency Bawaslu. Barru, then quantitative descriptive analysis was carried out. The results of the author's research found that: Law enforcement in regional head elections regarding campaigns carried out via social media in Barru Regency carried out by Candidate Pairs or Campaign Teams via social media can be carried out in an orderly manner influenced by the factors of the law and effective law enforcement in implementation. monitoring campaigns by regulations. However, there is still a lack of public awareness to be wise in using social media for campaigning. It is less effective because one of the law enforcement processes is through rehabilitation decisions at the Makassar District Court. There are still many victims of narcotics abuse who have not successfully undergone the rehabilitation process, thus causing victims to become dependent on narcotics. Factors that influence law enforcement against victims of narcotics abuse in the city of Makassar include: legal substance, legal structure and legal culture. Actions to prevent campaigns carried out via social media are that Candidate Pairs or Campaign Teams who use social media as a campaign tool use official social media accounts that have been registered with the General Election Commission.